Optimizing wave energy parks with over 1000 interacting point-absorbers using an approximate analytical method. (June 2015) - Göteman, Malin; Engström, Jens; Eriksson, Mikael; Isberg, Jan
Highlights: Circular park geometry is the best option for the studied large wave energy parks. Park with lowest power fluctuations has random geometry and variance v = 0.024 . Doubling number of devices from 50 to 100 WECs decrease fluctuations with 21%. Doubling number of devices from 100 to 200 WECs decrease fluctuations with only 19%. Increasing the WECs 32 times reduced variance by 5 and increased the power by 20. Abstract: Large arrays of wave energy converters of point-absorber type are studied using an approximate analytical model. The model is validated against a numerical method that takes into account full hydrodynamic interactions based on linear potential flow theory. The low computational cost of the analytical model enables parameter studies of parks in the MW range and includes up to over 1000 interacting devices. The model is actuated by irregular wave data obtained at the Swedish west coast. In particular, focus is on comparing park geometries and improving park configurations to minimize the power fluctuations.